Tradução comentada do capítulo XVIII do relato de viagem The exploration of the valley of the Amazon, de Herndon, para o português brasileiro - Queiroz, Rosilene Lima Cardozo de (2025)
This research aims to carry out translation into Brazilian Portuguese of Chapter XVIII of the book “The Exploration of the Valley of the Amazon”. Written by U.S. Navy Lieutenant William Lewis Herndon. The book consists of a travel account that describes the expedition carried out by the author in 1851, departing from Lima towards Para. The chapter in question details his one-month stay in Pará, offering a rich and detailed overview of the region at the time. In addition to the translation, which follows the ethical approach proposed by Antoine Berman, this work aims to elaborate explanatory notes on the chapter, critical comments on the translation process, and a critical analysis that explores the foreign perspectives, your colonizing intentions and the pre-existing concepts present in his narrative. The environmental characteristics addressed in the text allow the translation to be framed within the parameters of eco translation, as proposed by Cronin and further developed by Torres, an approach that values the ecological dimension and sustainability in the translation process. From this perspective, the study seeks to highlight the importance of travel accounts for understanding the Amazon and how eco translation can give space to nature and anthropic relations with the Amazonian environment. This work, therefore, not only promotes access to a relevant historical document but also reinforces the connection between translation, culture, and environment.